2010
DOI: 10.1179/030192309x12506804200582
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation study of ironmaking using biomass

Abstract: The economic advantage of using biomass as partial substitute for fossil reductants in the blast furnace (BF) process was studied by simulation. A thermodynamic model of the BF was used in combination with simple models of the coke plant, sinter plant, hot stoves, basic oxygen furnace and power plant. Pretreatment of the biomass before its injection in the BF is considered in a pyrolysis unit where the carbon content and heating value are raised and the oxygen content is lowered, which is beneficial for the BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…This is in perfect agreement with the observations presented in Fig. 3 and the results of Helle et al 12,13) where a partial conversion of the biomass with a pyrolysis temperature of about 250°C was found to be optimal. Thus, the local minima reported by Helle et al 12) with respect to the pyrolysis temperature have been efficiently avoided by the search.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…This is in perfect agreement with the observations presented in Fig. 3 and the results of Helle et al 12,13) where a partial conversion of the biomass with a pyrolysis temperature of about 250°C was found to be optimal. Thus, the local minima reported by Helle et al 12) with respect to the pyrolysis temperature have been efficiently avoided by the search.…”
Section: Resultssupporting
confidence: 82%
“…With the exception of the pyrolysis unit, all other unit processes are described by linear models. Helle et al 12,13) studied a similar system, but with one BF only, and analyzed how the price of biomass and emissions affected the optimal state of the system with respect to costs of liquid steel. Results from their study will also be used as a reference for the present investigation.…”
Section: Models Flows and Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Helle et al, 2010;Helle et al, 2009;Gupta, 2003;Suopajärvi and Fabritius, 2012; . Helle et al (2010) and Helle et al (2009) simulated partial substitution of fossil reducing agents with biomass in the BF. They concluded that the biomass had to be pre-processed through pyrolysis, because the high oxygen content and low heating value of raw biomass would reduce the productivity of the BF.…”
Section: Biomass As Reducing Agent and Fuelmentioning
confidence: 99%